INVESTIGATING THE EFFECTIVENESS AND LEARNER PERCEPTIONS OF THE WORDTHEME MOBILE APPLICATION FOR EFL VOCABULARY LEARNING - Jakbaraliyev Behruz Isroiljon o’g’li (Bright Mind Publishing, 2026)
The integration of mobile technologies into English as a Foreign Language (EFL) instruction has transformed traditional vocabulary learning approaches, offering learners interactive, flexible, and personalized experiences [1,2]. The Wordtheme mobile application provides structured features for vocabulary acquisition, including a personalized My Dictionary, search and cloud-based collaboration tools, teacher-guided word sharing, and multiple interactive revision activities such as flashcards, matching tasks, spelling exercises, listening-based tasks, and crosswords [3,4]. Despite its potential, limited empirical research has examined the app’s effectiveness and learners’ perceptions in secondary EFL contexts. This study investigates the impact of the Wordtheme application on vocabulary acquisition and explores learners’ perceptions of its instructional value among Uzbek secondary school students. A mixed-methods design was employed, combining pre- and post-tests to measure vocabulary gains and questionnaires to capture learners’ attitudes toward the application [5,6]. Findings indicate that the use of Wordtheme significantly enhanced vocabulary acquisition and was positively received by learners, who highlighted its usability, interactivity, and motivational features. These results suggest that mobile applications like Wordtheme can effectively supplement traditional vocabulary instruction and support autonomous, engaging learning experiences [7].
Keywords: Mobile-Assisted Language Learning, Vocabulary Acquisition, EFL, Wordtheme, Learner Perceptions.